Use of Tofu Waste as Food for Silver Worms (Tubifex sp) - Khusnul Khotimah; Helmizuryani Helmizuryani; Meika Puspita Sari; Elva Dwi Harmilia; Suyatno Suyatno; Rosmiah Rosmiah (Altifani Journal: International Journal of Community Engagement, 2023)
Silkworms (Tubifex sp) are a natural feed with high nutritional content and are needed by fish, especially in the fry phase to support fish growth. Therefore, knowledge of natural food cultivation is needed to support the success of fish farming. Silkworm cultivation requires media with high organic content. Tofu pulp waste is one of the media that can be utilized for silkworm cultivation.  The purpose of this activity is to increase community skills in silkworm cultivation by utilizing tofu pulp waste as a cultivation medium to provide natural feed for cultured fish carried out by the Bumdes fish farming group of Serdang Menang village, SP. Padang OKI. Padang OKI.  The method is carried out by conducting counseling and mentoring in making silkworm cultivation sites and how to cultivate silkworms. Community Service activities regarding the production of silkworm cultivation with a system of utilizing organic waste have been well understood by the community.  It is hoped that the community in Serdang Menang Village, SP. Padang Kab.OKI can apply it in fish farming activities.